Long-term effect of island industrial construction on groundwater health risk - Yong Huang; Daqing Wang; Haoli Xu; Zhao Lu; Zijian Cheng; Zhibin Ding; Yi Wang; Yue Shi; Huiru Cui; Xiaoying Lian (Ecological Indicators)
On some islands, the main source of residential water is groundwater, whose quality is seriously threatened by continuous industrial construction in island areas. However, there are few studies on the multivariate and spatiotemporal evaluation of the risk of island industrial construction to human health by threatening groundwater quality. Using an industrial park in Hainan as the study area, a model incorporating remote sensing cloud computing, the DRCSTLV model, the human health risk assessment (HHRA) model, and MODFLOW + MT3DMS + RT3D was established to provide a comprehensive assessment of health risks in the area from 2015 to 2022. The DRCSTLV model, which includes seven indicators along with associated potential health risks, is based on groundwater flow fields and pollutant transport models. The results of the comprehensive groundwater health risk assessment from 2015 to 2022 revealed that the annual maximum normalized health risk of groundwater in the study area show an overall fluctuating upward trend. The highest health risk values were stabilized by 2020, and the evaluation results for 2021 and 2022 increased slightly. However, the health risk in the center of the park reached Level 1 and above, and the risk area of Level 2 and above covered an area of up to 94,613 m2, accounting for 0.0039 of the entire study area. Finally, Monte Carlo simulations were used to conduct uncertainty and sensitivity analyses to reflect the objective reality of groundwater health risks under the combined influence of various uncertainty factors. The analysis revealed that the contributions of indicators D and L to the uncertainty were the highest. In addition, the diffusion of chemical oxygen demand in the vicinity of pollution sources has a significant impact on uncertainty. These findings provide valuable guidance for the prevention and control of groundwater pollution in island regions.